2010
DOI: 10.1007/s00521-010-0501-6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks workflow and its application in the petroleum industry

Abstract: We develop a neural network workflow, which provides a systematic approach for tackling various problems in petroleum engineering. The workflow covers several design issues for constructing neural network models, especially in terms of developing the network structure. We apply the model to predict water saturation in an oilfield in Oman. Water saturation can be accurately obtained from data measured from cores removed from the oil field, but this information is limited to a few wells. Wireline log data are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…The back-propagation algorithm is considered as the most widely used algorithm [17]. Associated with the feed-forward ANN architecture, this consists of propagating a signal from input to output, and updating the whole cycle retrospectively after obtaining the error value resulting in the comparison of the calculated value(s) to the real value(s).…”
Section: Ann Structure and Modelmentioning
confidence: 99%
“…The back-propagation algorithm is considered as the most widely used algorithm [17]. Associated with the feed-forward ANN architecture, this consists of propagating a signal from input to output, and updating the whole cycle retrospectively after obtaining the error value resulting in the comparison of the calculated value(s) to the real value(s).…”
Section: Ann Structure and Modelmentioning
confidence: 99%
“…The network normally consists of several layers, which can be an input layer, an output layer, and one or more hidden layers [34,35]. Fundamentally, the layers connect with each other by a linking system, which can be represented principally by weights, biases, and activating functions that are applied directly to the neurons of each layer [36].…”
Section: Ann Structurementioning
confidence: 99%
“…Several relationships or rules of thumb exist in literatures relating the training-dataset size to some user-defined error parameters calculated for a given network configuration (Waszczyszyn, 1999;Xu & Chen, 2008). A recent review of a range of design issues related to ANN development in petroleum industry can be found in Al-Bulushi, King, Blunt, and Kraaijveld (2012). It was demonstrated that a single hidden layer could approximate any function with finite number of discontinuities (Kröse, Krose, van der Smagt, & Smagt, 1993).…”
Section: Artificial Neural Networkmentioning
confidence: 99%